2021
DOI: 10.3856/vol49-issue4-fulltext-2509
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of Euphausia mucronata: development stages and its relationship with temperature and chlorophyll-a concentration

Abstract: Euphausia mucronata abundance and distribution of the developmental stages (calyptopis, furciliae, juveniles, and adults) was analyzed as a function of seawater temperature and chlorophyll-a concentration between Paposo (25°S) and Coquimbo (30°S), Chile. Zooplankton samples were obtained using bongo nets during February of three consecutive years (2014-2016). The Q coefficient was used to explore the relationship between the distribution and abundance of the development stages of E. mucronata with the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In general, our results suggest that chlorophyll-a concentration remains sufficiently high to support large euphausiid populations off northern Chile and is not a controlling factor of krill species abundances and distribution, at least at the spatial and temporal scales covered in this study. Gonzaĺez et al (2021) found no relationship between chlorophyll-a concentration and Humboldt krill developmental stages. However, to properly determine whether there is food limitation, it is necessary to incorporate food ingestion rates (Antezana, 2010), growth rates (Riquelme-Bugueño et al, 2016), and biomass production (Riquelme-Bugueño et al, 2013) in future studies, to observe changes in these population parameters under different productivity scenarios.…”
Section: Impacts Of Thermal Fluctuations Food Availability Advection ...mentioning
confidence: 76%
See 1 more Smart Citation
“…In general, our results suggest that chlorophyll-a concentration remains sufficiently high to support large euphausiid populations off northern Chile and is not a controlling factor of krill species abundances and distribution, at least at the spatial and temporal scales covered in this study. Gonzaĺez et al (2021) found no relationship between chlorophyll-a concentration and Humboldt krill developmental stages. However, to properly determine whether there is food limitation, it is necessary to incorporate food ingestion rates (Antezana, 2010), growth rates (Riquelme-Bugueño et al, 2016), and biomass production (Riquelme-Bugueño et al, 2013) in future studies, to observe changes in these population parameters under different productivity scenarios.…”
Section: Impacts Of Thermal Fluctuations Food Availability Advection ...mentioning
confidence: 76%
“…However, those years did not exhibit proportional changes in productivity. In particular, the abundance of the upwelling-associated Humboldt krill species (Riquelme-Bugueño et al, 2012;Gonzaĺez et al, 2021) had significantly higher abundances during the years with the most negative temperature anomalies (late 2010, 2014, and 2017). These interannual abundance fluctuations were probably caused by distribution displacements driven by poleward water-mass advection and/or by coastal trapped waves linked to ENSO events, as it has been proved in the CCS (Lilly and Ohman, 2021).…”
Section: Impacts Of Thermal Fluctuations Food Availability Advection ...mentioning
confidence: 98%